Sufism in eighteenth-century India: Muḥammad Nāṣir ʻAndalīb's Lament of the Nightingale and Ṭarīqa-yi Khāliṣ Muḥammadiyya - Saghaee, Neda (Routledge Sufi series, 2023)
"This book explores the convergence and interrelation of the text of with its context. It considers the development of the notion of the as an intellectual achievement in the history of ideas in Islam generally and also as an important part of Sufism in South Asia"--